Rationale and clinical results of inhibiting interleukin-5 for the treatment of severe asthma - Berair, R; Pavord, I (2013)
Severe asthma is responsible for considerable morbidity and a high proportion of the healthcare costs attributable to asthma. Management is not straightforward as the clinical, pathological and physiological features are heterogeneous and the relationships between these features are poorly understood. In recent years significant progress has been made in understanding this heterogeneity and eosinophilic asthma has emerged as a potentially clinically important phenotype because treatment with monoclonal antibodies against IL-5 is effective. This has required a change in our understanding of the role of eosinophilic airway inflammation in airways disease and the developments of reliable biomarkers of eosinophilic airway inflammation. We will review these developments and describe the clinical experience so far with treatment with monoclonal antibiotics against IL-5. © 2013 Springer Science+Business Media New York.